The Physicomechanical Deterioration Characteristics and Mesoscopic Damage Analysis of Sandstone under Acidic Environment - Runke Huo; Tian Qiu; Yanling Liang; Shuguang Li; Meiting Qian (Advances in Civil Engineering)
The physicomechanical deterioration characteristics of sandstone subjected to H2SO4, HCl, and H2O solutions of different pH values are studied by the method of long-term accelerated immersion. The quantitative relationships between the damage variables based on CT (computer tomographic identification technology) numbers and the immersion time, the uniaxial compressive strength, the peak point strain, and the elastic modulus of rock samples are analyzed. The test results indicate that the pH value of immersion solutions, the dissolution rate of Ca2+ and Na+, and the quality change of rock samples show visible stage characteristics under acidic environment. With the soaking time extended, the pH value of solutions increases gradually, and the quality change of rock samples decreases gradually. The smaller the pH value of immersion solutions is, the higher the dissolution rate of Ca2+ and Na+ is. However, the cation dissolution rate under a weak acid environment with a high pH value has little difference with that under the distilled water (pH = 7). With the increase of the soaking time and the acidity, the compaction stage of rock samples becomes longer, the elastic stage becomes shorter, the deterioration degree of mechanical parameters becomes more extensive, and the destruction of sandstone samples shows ductility characteristics increasingly. The corrosion degree of corroded sandstone samples is quantitatively represented by microscopic damage variables based on CT numbers. The regression analysis results show that damage variables of acid-corroded sandstone samples have a power function relationship with soaking time and an exponential function relationship with peak strength, peak point strain, and elastic modulus.